(untitled) (The International Journal of Educational Sciences and Arts, 2025)
The study aims to monitor the performance of content creators on digital broadcasting platforms and their compliance with regulations and laws in the Kingdom of Saudi Arabia. It also aims to determine how they adhere to these regulations and laws throughout their media careers. The study relied on the descriptive-analytical approach, which relies on describing and analyzing real-life phenomena to understand their causes and interrelationships. The researcher sought to understand their level of awareness of the regulations and laws governing digital media work, and their degree of compliance with them. Furthermore, the study examined the differences between content creators’ degree of compliance with regulations and laws according to their employer, whether they work under the umbrella of official media entities or work freely without being bound by institutional work. This was achieved by using a questionnaire as a data collection tool, applied to a sample of (100) content creators in the Kingdom of Saudi Arabia. The study reached a set of results, the most prominent of which are: The relatively high positive trends in content creators’ perceptions of their degree of compliance with regulations and laws on digital streaming platforms are evident, as there was a significant increase in the arithmetic averages of statements. Representing positive trends regarding compliance with regulations and laws in the content industry.